2020
DOI: 10.1016/j.gr.2019.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The age of the Tashinga Formation (Karoo Supergroup) in the Mid-Zambezi Basin, Zimbabwe and the first phytosaur from mainland sub-Saharan Africa

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 63 publications
1
38
0
Order By: Relevance
“…2015; but see Barrett et al . 2020). Our results broadly support this hypothesis, suggesting that temnospondyls were constrained in the range of palaeoclimatic conditions they occupy (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2015; but see Barrett et al . 2020). Our results broadly support this hypothesis, suggesting that temnospondyls were constrained in the range of palaeoclimatic conditions they occupy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2013; Stocker & Butler 2013; Barrett et al . 2020). In particular, the absence of phytosaurs from well‐sampled deposits in Argentina and South Africa is hypothesized to have been linked to local climate conditions in south‐western Pangea (Brusatte et al .…”
Section: Discussionmentioning
confidence: 99%
“…We believe this formation to be named after Tashinga Camp (in Matusadona National Park), although not all of the relevant lithologies are exposed there. The use of the Tashinga Formation was recently applied to outcrops along the shoreline of Lake Kariba by Barrett et al (2020). In contrast, Ait-Kaci Ahmed (2018) suggested that the Upper Karoo Group could be divided into the Escarpment (composed of the Escarpment Grit and Fine Red Sandstone members), Pebbly Arkose and Forest Sandstone formations (Fig.…”
Section: Historical Reviewmentioning
confidence: 99%
“…These were discovered on an island in the Bumi River estuary (c. 16°51 0 S; 28°28 0 E) and reported by Bond (1974;Raath et al 1992). Recently, Barrett et al (2020) documented the first fossil assemblage from the upper part of the 'Tashinga Formation' (dominated by phytosaurs, lungfish and metoposaurid amphibians) and provided a maximum depositional age of 209 ± 4.5 Ma (LA-ICPMS; see Barrett et al 2020; see also online Supplementary Table S1, available at http://journals. cambridge.org/geo) for these assemblages along the southern shoreline of Lake Kariba.…”
Section: D Pebbly Arkose Formationmentioning
confidence: 99%
See 1 more Smart Citation